Neurologic disorders in long-term survivors of neuroblastoma – a population-based cohort study within the Adult Life after Childhood Cancer in Scandinavia (ALiCCS) research program. (1st February 2020) - Norsker, Filippa Nyboe; Rechnitzer, Catherine; Andersen, Elisabeth Wreford; Linnet, Karen Markussen; Kenborg, Line; Holmqvist, Anna Sällfors; Tryggvadottir, Laufey; Madanat-Harjuoja, Laura-Maria; Øra, Ingrid; Thorarinsdottir, Halldora K.; Vettenranta, Kim; Bautz, Andrea; et al.
Abstract: Background: Neuroblastoma is the commonest extracranial solid tumor of childhood, yet rare, and with poor survival before 1990, especially for high-risk disease; thus, information on late effects is sparse. With great advances in cancer treatment, survival has reached 80% in the Nordic countries. The aim of the study was to investigate the risk of developing neurologic disorders after neuroblastoma. Material and methods: Through population-based cancer registries of four Nordic countries we identified 654 5-year survivors of neuroblastoma (diagnosed 1959–2008) and 133, 668 matched population comparisons. We grouped neurologic diagnoses from national hospital registries into 11 main diagnostic categories and 56 disease-specific sub-categories and calculated relative risks (RRs), absolute excess risks (AERs), cumulative incidence and mean cumulative count (MCC). Information on cancer treatment was available for 49% of survivors. Results: A hospital contact for a neurologic disorder was observed in 181 survivors 5 years or more from cancer diagnosis with 59 expected, yielding a RR of 3.1 (95% CI 2.7–3.6) and an AER of 16 per 1, 000 person-years (95% CI 12–19). The most frequent disorders included epilepsy, paralytic syndromes, diseases of the eyes and ears and hearing loss. The cumulative incidence of any neurologic disorder was 31% in survivors 20 years after cancer diagnosis with a MCC of 0.5 unique diagnoses. All risks were highest in survivors of high-risk neuroblastoma. Conclusion: Neuroblastoma survivors represent a population with a high risk of developing neurologic disorders. Our results should contribute to improving health care planning and underscores the need for systematic follow-up care of this vulnerable group of survivors.